PERLINDUNGAN LINGKUNGAN DALAM UU CIPTA KERJA - Reyhandhi Alfian Muslim; Fatma Ulfatun Najicha (Indonesian State Law Review, 2022)
On October 5, 2020, the Indonesian government passed the Omnimbus Law which contained various kinds of legislation. Including the environment which is also regulated in the Omnimbus Law. On the one hand, this regulation provides hope for Indonesia's economic growth. However, on the other hand, this regulation has the potential to damage the environment and is not in line with the Indonesian Government's commitment to reduce greenhouse gas (GHG) emissions, which in it weakens instruments for environmental protection and management. Weakening of environmental instruments has the potential to increase greenhouse gas emissions through high-carbon activities and investment in fossil energy. Therefore, this paper will critically analyze how the weakening of environmental instruments in the Omnimbus Law and the Revision of the Minerba Law hampers the fulfillment of Indonesia's greenhouse gas emission reduction targets in the era of restoring national economic stability.